Picture fuzzy WASPAS technique and its application in multi-criteria decision-making - Senapati, Tapan; Chen, Guiyun (Soft computing (Berlin, Germany), 2022)
In recent times, multi-criteria decision-making (MCDM) strategies have grown in popularity as the world has become more unpredictable. The objective of this article is to establish a WASPAS (weighted aggregated sum product assessment)-based outranking approach for MCDM in a picture fuzzy set (PFS) environment. To illustrate the practicality and reasonableness of the suggested method, in reality, scenario research involving appropriate air-conditioning system selection is provided. The recommended technique performs well when contrasted to other existing classifier strategies, according to experimental results acquired for a real-world issue.